Emergence of antibiotic resistance due to the excessive use of antibiotics in medicines and feed additives: A global scenario with emphasis on the Indian perspective - R Mithuna; R Tharanyalakshmi; Ishan Jain; Shivangi Singhal; Divyanshu Sikarwar; Sovik Das; J. Ranjitha; Devanita Ghosh; Mohammad Mahmudur Rahman; Bhaskar Das (Emerging Contaminants)
Antibiotics were discovered for medicinal applications, notably in the last century and since then, they have been prevalently employed for prophylactic purposes in various sectors in the last few decades. Due to the non-judicial usage of antibiotics in sectors like agriculture, aquaculture, and animal husbandry, and as therapeutic substances, antibiotics have started to become a nuisance for the environment and human beings. Furthermore, the accumulation of antibiotics in the biosphere has led to the development of antibiotic resistance in microorganisms making it difficult to treat a growing number of infections. Hereafter to understand the holistic picture of the impacts associated with antibiotics on the environment, the evolution of individual antibiotic pathways for therapeutic and non-therapeutic purposes needs to be studied along with their effect on the environment. Most of the recent reviews on antibiotics either concentrate on a particular source, pathway or environmental impact; however, the present state-of-the-art review attempts to summarize and update the possible sources of antibiotics, usage, their impact on humans, and environmental health on a global scale with a special emphasis on India. Also, there is a critical discussion about the various methods employed for the removal of antibiotics from an array of sources, on both water and soil matrix. The review finally emphasize that the implication of stringent regulation and selection of appropriate technology are required to alleviate antibiotics menace from the environment.